2017
DOI: 10.1016/j.midw.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

How do women feel about being weighed during pregnancy? A qualitative exploration of the opinions and experiences of postnatal women

Abstract: these findings contribute to the current debate about the re-introduction of routine weighing throughout pregnancy (Allen-Walker et al., 2016). Women stated that they expected to be weighed during pregnancy and, contrary to previous claims, there was no evidence that routine weighing during antenatal care caused anxiety. From discussions it was clear that women desired more information on gestational weight gain and a healthy lifestyle, and felt that health professionals should provide this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
3
7
0
Order By: Relevance
“…Nevertheless, many women expressed dissatisfaction about the amount or lack of information they received from pregnancy care providers about weight management, wanted more weight management information and support during pregnancy and postnatally, and felt that this should be incorporated into routine care. These findings are consistent with others that have highlighted the lack of consistent and reliable information women receive from pregnancy and postnatal care providers about weight management [ 25 , 26 , 30 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, many women expressed dissatisfaction about the amount or lack of information they received from pregnancy care providers about weight management, wanted more weight management information and support during pregnancy and postnatally, and felt that this should be incorporated into routine care. These findings are consistent with others that have highlighted the lack of consistent and reliable information women receive from pregnancy and postnatal care providers about weight management [ 25 , 26 , 30 ].…”
Section: Discussionsupporting
confidence: 91%
“…Nonetheless, weighing practices revealed in this study were inconsistent and many women reported that they had expected to be weighed throughout their pregnancy. This is consistent with other studies where women have expressed a preference for more frequent weighing and believe that it should be part of standard pregnancy care as it would provide reassurance and motivation for weight management in pregnancy and postnatally [ 26 , 35 ]. Furthermore, pregnancy care providers in a recent Australian study suggested that weighing all women would avoid stigmatising those who are overweight or obese [ 31 ].…”
Section: Discussionsupporting
confidence: 89%
“…NICE noted the lack of evidence of benefit, but also expressed concerns that weighing may cause psychological harm. There was no evidence to indicate any health harms in this trial and other studies suggest that, far from increasing anxiety, it is welcomed by women 12 20…”
Section: Discussionmentioning
confidence: 60%
“…Pregnant women have reported that they expect to be weighed during pregnancy and feel that it should be part of routine antenatal care 12 20. However, three previous trials have investigated the effectiveness of behavioural interventions based on regular weighing to prevent excessive gestational weight gain and none of them were effective 7–10.…”
Section: Discussionmentioning
confidence: 99%
“…The development of interventions to help women avoid excessive gestational weight gain is a UK public health priority (National Institute for Health and Clinical Excellence, 2010). Women also expect their weight to be monitored during pregnancy (Daley et al, 2015) and believe it to be beneficial (Allen-Walker et al, 2017). Global recommended practice on the regularity of weighing pregnant women varies (Scott et al, 2014).…”
Section: Introductionmentioning
confidence: 99%